KEDUDUKAN ISTERI BEKERJA DALAM MENGURUS KELUARGA PERSPEKTIF HUKUM ISLAM - Reza Fahlevi Nurpaiz; Syaik Abdillah; Dahwadin Dahwadin; Dwi Reiza Meinanti (Mutawasith: Jurnal Hukum Islam, 2020)
The role of women in the family has a very complex dimension. In different times and conditions, women are more of a major breadwinner. The research aims to analyse the effects of family problems on women who work, analyzing the influence of women working on family harmony and analyzing the pattern of liability and rights in the family. This research is conducted using normative juridical methods. The approach used is sociological which focuses on change and social structure. From the data on the analysis of researchers showed that the influence of family problems in women who work is, 1). Feeling depressed 2). Exhausted, tired 3). Stress. While the influence of women working towards the harmony of family, among others, the occurrence of divorce, the neglect of the rights of husbands and children, as for the pattern of the rights and obligations in families in women who work among others (1). Meeting daily needs: preparing food needs such as eating, drinking, and cleaning the house. (2). Meet the needs of Bilogis and the need for effction or compassion. And the pattern of husband and wife relationship, especially in the aspect of the division of work and decision-making after the change of role in the family including: first, to the husband, (1). Difficult to divide time (2). Less role in paying attention to husbands. Second, to the child. (1). The neglect of the children at home, (2). Mothers are not always in the important moments, (3). Not all child needs are met. It can thus be concluded that the law of a wife making a living outside of the house is permissible, provided she does not neglect her duties as a mother. But rather when wives neglect their primary duties. Thus the view of Islam to the wife is not permissible or unclean because it will affect the integrity of the household in creating a family of Sakinah, Mawaddah, and Rahmah.